Human rights violations among men who have sex with men and transgender people in South Africa - Raymond Chimatira; Dumo Jebese-Mfenqe; Joram Chikwanda; Edward Sibanda; Qhawekazi Thengwa; Bulumko Futshane; Sisanda Gaga (AOSIS, 2023)
Background: Men who have sex with men (MSM) and transgender (TG) people face human rights violations (HRVs) which impact their access to critical interventions for HIV prevention, treatment, and related services. Objectives: This study describes how Beyond Zero, a not-for-profit organisation in South Africa built an HRV reporting system and discusses data on the HRVs experienced by MSM and TG people who accessed HIV prevention services between 01 January 2021 and 31 December 2021. Method: This was a cross-sectional study using secondary analysis of programmatic data routinely collected as part of HIV prevention programmes for MSM and TG in 10 rural districts of South Africa. Results: A total of 249 individuals reported having experienced HRVs. Of these, 113 (54.6%) were physical violations, 145 (58.2%) were psychosocial harassment, 15 (18.3%) were experienced within the workplace, and 59 (23.7%) were experienced at a healthcare or social services institution. Overall, 77% of the physical violations and 70.4% of the psychosocial violations occurred in the home and local community settings; 76.1% of the perpetrators of physical violence and 79.3% of the perpetrators of psychosocial harassment were known. Most incidents of physical violence (80.5%) and psychosocial harassment (92.4%) were not reported due to fear of homophobic or transphobic violence. Conclusion: Our findings demonstrate the feasibility of documenting HRVs among MSM and TG people within HIV prevention programmes. Men who have sex with men and TG people should be systematically screened for HRVs and linked to legal or other services. Contribution: Our findings present data on the nature of HRVs in 10 districts outside of the large urban centres where research documenting the lived experiences of MSM, TG people and other key populations is traditionally conducted in South Africa. Such data contribute to addressing the gap in the literature on the needs of MSM and TG people in South Africa caused by the delayed inclusion of rural MSM and TG people in research.